A Brief Overview of the Rapid Progress and Proposed Improvements in Gallium Nitride Epitaxy and Process for Third-Generation Semiconductors with Wide Bandgap - An-Chen Liu; Yung-Yu Lai; Hsin-Chu Chen; An-Ping Chiu; Hao-Chung Kuo (Micromachines, 2023)
In this paper, we will discuss the rapid progress of third-generation semiconductors with wide bandgap, with a special focus on the gallium nitride (GaN) on silicon (Si). This architecture has high mass-production potential due to its low cost, larger size, and compatibility with CMOS-fab processes. As a result, several improvements have been proposed in terms of epitaxy structure and high electron mobility transistor (HEMT) process, particularly in the enhancement mode (E-mode). IMEC has made significant strides using a 200 mm 8-inch Qromis Substrate Technology (QST®) substrate for breakdown voltage to achieve 650 V in 2020, which was further improved to 1200 V by superlattice and carbon-doped in 2022. In 2016, IMEC adopted VEECO metal-organic chemical vapor deposition (MOCVD) for GaN on Si HEMT epitaxy structure and the process by implementing a three-layer field plate to improve dynamic on-resistance (RON). In 2019, Panasonic HD-GITs plus field version was utilized to effectively improve dynamic RON. Both reliability and dynamic RON have been enhanced by these improvements.